How Large are Road Traffic Externalities in the City? The Highway Tunneling in Maastricht, the Netherlands - Joep Tijm; Thomas Michielsen; Raoul van Maarseveen; Peter Zwaneveld (Center for Economic Studies and ifo Institute (CESifo), 2018)
Infrastructure projects are increasingly aiming to improve liveability, in particular in urban areas. We analyse a specific case in which an existing highway in an urban area was moved underground in order to improve intercity traffic flows and to reduce traffic externalities. As travel times within the city hardly changed, this allows for a clean identification of the value of traffic externalities. We find that the liveability benefits of such integrated infrastructure are substantial relative to the construction costs. Each halving of distance to the tunneled segment is associated with 3.5% more appreciation in house prices since the start of the project.
Keywords: H40; R20; R40; 330